2005
DOI: 10.1093/brain/awh624
|View full text |Cite
|
Sign up to set email alerts
|

Role of return migration in the emergence of multiple sclerosis in the French West Indies

Abstract: The emergence of multiple sclerosis in island societies has been investigated only in a few Caucasian populations living in temperate regions. The effect of human migration on the risk of developing this disease is still an open question because of possible genetic selection. We conducted an epidemiological study of the multiple sclerosis population in the French West Indies (Martinique and Guadeloupe), a population which includes large numbers of West Indians who have returned after emigrating to metropolitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 36 publications
2
82
2
2
Order By: Relevance
“…Epidemiological investigation revealed a dichotomous relationship between the global distribution of MS and parasitic infections (Fleming & Cook 2006). Also, longitudinal and migratory studies of MS have been consistent with the hygiene hypothesis, showing a paralleled increase in MS and improved sanitation (Cabre et al 2005). In this context we evaluated the presence of worm eggs in the feces and adult worms in the intestine of Lewis rats from both colonies.…”
Section: Discussionmentioning
confidence: 79%
“…Epidemiological investigation revealed a dichotomous relationship between the global distribution of MS and parasitic infections (Fleming & Cook 2006). Also, longitudinal and migratory studies of MS have been consistent with the hygiene hypothesis, showing a paralleled increase in MS and improved sanitation (Cabre et al 2005). In this context we evaluated the presence of worm eggs in the feces and adult worms in the intestine of Lewis rats from both colonies.…”
Section: Discussionmentioning
confidence: 79%
“…[18][19][20] Some studies have shown that individuals who migrate before puberty have the incidence of MS in the area to which they have migrated. [20][21][22] This suggests a possible interaction between the ethnic origin of the patient, the latitude, and whatever is the factor (or factors) that triggers MS. Other studies have suggested that less sun exposure at increasing latitude might be a risk factor for MS, 23,24 and vitamin D deficiency is an additional potential explanation for some of the epidemiological differences in MS. 25,26 In addition, an increased incidence of ON during the spring season has been reported. 27,28 There are also some who postulate viruses as having a role in the pathogenesis of MS. 29,30 Diagnosis Clinical presentation (signs and symptoms)…”
Section: Epidemiologymentioning
confidence: 97%
“…8,9,13,14 Only Class IV studies are available regarding the association between ethnicity and the cause of myelitis. 15,16 When comparing various types of myelitis, we found 2 studies showing no significant age differences and 2 studies with insufficient data to assess age differences concerning idiopathic TM vs MS presenting as myelitis (table e-2).…”
Section: Analysis Of Evidencementioning
confidence: 99%